"Extended subcutaneous route" technique: a quick subcutaneous tunnelling technique for PICC insertion. Issue 3 (May 2017) - Elli, Stefano; Abbruzzese, Chiara; Cannizzo, Luigi; Vimercati, Simona; Vanini, Stefania; Lucchini, Alberto
Purpose: To describe a quick tunnelling technique for peripherally inserted central catheter (PICC) insertion called the "extended subcutaneous route" technique. Methods: The "extended subcutaneous route" technique is described step by step. Results: In 18 consecutive PICCs, inserted with extended route technique in ASST Monza, no complications during insertion were registered. In 969 catheter days observed, we identified only one accidental dislodgement. No other mid-term complications were observed. Conclusions: Extended subcutaneous route technique allows the creation of a subcutaneous tunnel <5 cm, without skin incision and additional manipulation. Extended subcutaneous route technique may be feasible and useful, particularly for patients with high risk of bleeding or infection.